2010
DOI: 10.1016/j.etp.2009.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water-soluble flavonoids, quercetin-5′-sulfonic acid sodium salt and morin-5′-sulfonic acid sodium salt, on antioxidant parameters in the subacute cadmium intoxication mouse model

Abstract: , et al.. Influence of water-soluble flavonoids: Quercetin5'-sulfonic acid sodium salt and morin-5'-sulfonic acid sodium salt on antioxidant parameters in the subacute cadmium intoxication mouse model. Experimental and Toxicologic Pathology, Elsevier, 2010, 62 (2) Cite this article as: Ewa Chlebda, Jan Magdalan, Anna Merwid-La Rd, Małgorzata Trocha, Maria Kopacz, Anna Kuźniar, Dorota Nowak and Adam Szela R g, Influence of water-soluble flavonoids: Quercetin-5'-sulfonic acid sodium salt and morin-5'-sulfonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…Furthermore, NaQSA and NaMSA, due to the ability to chelate metals ions, have been applied in the studies on detoxification of mercury, cadmium, and lead in rats [11][12][13]. It is worth emphasizing that NaQSA and NaMSA exert low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NaQSA and NaMSA, due to the ability to chelate metals ions, have been applied in the studies on detoxification of mercury, cadmium, and lead in rats [11][12][13]. It is worth emphasizing that NaQSA and NaMSA exert low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effect of NaMSA administration on decreased GSH level in mice liver was observed in subacute cadmium poisoning described in our previous work. 18 Moreover, in earlier experiment of Ray et al 30 antioxidant action of naturally occurring morin was revealed in CPX/ flutamide-induced lipid peroxidation. Flavonoid constituents of citrus extract (Citrus aurantium var.…”
Section: Discussionmentioning
confidence: 96%
“…Such action of NaMSA is difficult to explain, because natural flavonoids as well as their synthetic derivatives are considered as antioxidative compounds. 12,17,18 In our earlier work, NaMSA given alone did not influence oxido-redox state parameters in mice but reversed unfavorable changes in LPOs level caused by subacute cadmium intoxication. 17 Single reports also indicated antiperoxidative potential of morin on CPX/flutamide-induced lipid peroxidation in rabbits confirmed by MDA level.…”
Section: Discussionmentioning
confidence: 98%
“…Different compounds were tested in animal models as antagonists of Cd, but information regarding their effects on Cd-induced alterations in spleen function is still sparse (Blanuša et al, 2005;Nemmiche et al, 2007;Luchese at al., 2007;Gong at al., 2008;Shukla and Kumar, 2009;Manna et al, 2009;Fouad at al., 2009;Sinha et al, 2009;Flora and Pachauri, 2010;Chlebda et al, 2010;Saljooghi and Fatemi, 2010;Sinicropi et al, 2010). Our recent studies demonstrated that monensin (a polyether…”
Section: Demonstrated That This Metal Inhibited Cell Proliferative MImentioning
confidence: 97%